OPTIMASI KINERJA DATABASE MENGGUNAKAN TEKNIK INDEXING DAN CACHING - Wildan Jazuli; Raka Hikmah Ramadhan; Robbi Kharisma Ar Rasyid (Yayasan Pendidikan Cahaya Budaya Indonesia, 2024)
The database is a critical component of an information system, serving as the medium for data storage and management. As the volume of stored data increases, database performance may degrade due to longer response times when executing queries. Therefore, optimization techniques such as indexing and caching are required to improve data access efficiency. This article discusses the concepts, implementation, and benefits of indexing and caching techniques in optimizing database performance. The method used in this study is a quantitative experimental approach, which involves measuring query execution times before and after applying indexing and caching on a relational database system using MySQL and Redis.